(untitled) (Vietnam Journal of Community Medicine, 2025)
Candida spp. is a common causative agent of oral thrush in immunocompromised patients. Objective: To determine the prevalence of oropharyngeal candidosis in HIV patients and related factors. Subject and method: A cross-sectional descriptive study on 52 HIV-positive patients undergoing outpatient treatment at Thuan An City Medical Center, Binh Duong Province from 12/2023-06/2024. Results: Patients with HIV accounted for the highest proportion (40.4%, 21/52) in the age group of 18-24 years and mainly men (90.4%, 47/52). The majority of patients have permanent addresses in Binh Duong (96.1%), secondary education level accounts for 44.2% (23/52) and the main occupation is workers accounting for 50% (26/52). The subjects of the disease belong to the group of man sex man, accounting for 76.9% (40/52). There were 30 (57.7%) patients positive for Candida spp and C. albicans species predominated (86.667%, 26/30). There is no association between the status of oropharyngeal candidosis in HIV-infected patients and related factors. Conclusions: High prevalence of oral and pharyngeal oropharyngeal candidosis in HIV-infected patients.